National Survey of Victim Service Providers, (United States), 2019 ([Verlag nicht ermittelbar], 2021)
The Bureau of Justice Statistics (BJS) entered into a cooperative agreement with Westat to design and conduct the National Survey of Victim Service Providers (NSVSP). The NSVSP is jointly funded by the Office for Victims of Crime (OVC) and BJS. It is part of BJS's Victim Services Statistical Research Program that aims to provide comprehensive information about what services are being provided to victims, who is being served, and what gaps in service delivery may exist. The NSVSP provides a critical opportunity to address the existing knowledge gaps and enhance the victim services field to better serve the needs of crime victims. It collected detailed information on the number of victims served by type of crime, victim characteristics, services provided, criminal justice and community relationships, service gaps, and VSP staff size, turnover, and characteristics.